2015
DOI: 10.1007/s00709-015-0829-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of imiquimod-induced psoriasis-like dermatitis in mice by herbal extracts from some Indian medicinal plants

Abstract: Psoriasis is a chronic autoimmune human skin disorder that is characterized by excessive proliferation of keratinocytes, scaly plaques, severe inflammation and erythema. The pathophysiology of psoriasis involves interplay between epidermal keratinocytes, T lymphocytes, leukocytes and vascular endothelium. Increased leukocyte recruitment and elevated levels of cytokines, growth factors and genetic factors like interleukin (IL)-1β, IL-6, IL-17, IL-22, IL-23, tumour necrosis factor (TNF)-α, interferon (IFN)-γ, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 60 publications
1
21
0
1
Order By: Relevance
“…These finding suggests that isoflavones in raw soybean are increased through the process of fermentation, this is considered to affect alleviation of inflammation. Recently, it was reported that artemisia have an anti-inflammatory effect in psoriasis animal model [67]. Therefore, in our result of change through fermentation, anti-inflammatory effect of Douchi may be associated with artemisia extract.…”
Section: Discussionmentioning
confidence: 57%
“…These finding suggests that isoflavones in raw soybean are increased through the process of fermentation, this is considered to affect alleviation of inflammation. Recently, it was reported that artemisia have an anti-inflammatory effect in psoriasis animal model [67]. Therefore, in our result of change through fermentation, anti-inflammatory effect of Douchi may be associated with artemisia extract.…”
Section: Discussionmentioning
confidence: 57%
“…They were then sacrificed on day 17 at the laboratory. Central dorsal skin tissue (approximately 1 cm 2 ) and right ear pinna from all the groups were excised for histological studies [ 23 ] and cytokine production analysis [ 20 ]. Blood samples from all the groups were collected in clean dry vials for cytokine production analysis [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, IFN-γ and IL-15 seem to increase the apoptotic resistance of the keratinocytes [15,16]. Also growth factors and genetic factors like transforming growth factor (TGF)-β, toll-like receptor (TLR)-2, signal transducer and activator of transcription (STAT-3), coiled-coil alpha-helical rod protein 1 (CCHCR1), steroidogenic acute regulatory protein (StAR), and vitamin D receptor (VDR) are suggested to be the most critical factors governing the exacerbation of psoriasis [17,18]. The essential transcription factor in psoriasis, nuclear factor kappa B (NF-κB), has been shown to be a key regulatory element occurring in a variety of immune and inflammatory pathways, in cellular proliferation and differentiation, and in apoptosis [19].…”
Section: Pathology Of Psoriasismentioning
confidence: 99%
“…Herbal products treatment of psoriasis through inhibition of cytokines was also confirmed in animal-based studies. The topical application of a mixture of herbal extracts (Tinospora cordifolia, Curcuma longa, Celastrus paniculatus, Aloe vera) lead to the downregulation of overexpressed cytokines in mice, initially induced with psoriasis-like dermatitis through topical application of imiquimod [17]. Some research found that phosphorylase kinase (PhK) enzyme is expressed on a significantly higher level in psoriatic epidermis as in normal epidermis [76].…”
Section: Mechanisms Of Action Of Herbal Products Used In Psoriasis Trmentioning
confidence: 99%